Analysis of the relationship between mining export and economic growth in Zimbabwe (1985) TO (2016) - Sundirai, Kudzanai (Midlands State University, 2020)
This research investigated the relationship between the mining export and economic growth in Zimbabwe using time series data for the period 1985 to 2016 as well as employing the Ordinary Least Squares (OLS) approach. The study was aiming at examining the impact of mineral export on economic growth in Zimbabwe. The results obtained showed that mineral export, real growth in agriculture, population growth and tax revenue significantly affect economic growth. Moreso the results also showed that real growth in manufacturing and inflation have insignificant influence on the economic growth of Zimbabwe. Basing on the findings, the research proposes The at enhancement of the mining sector export will largely contribute to the economic growth of the country given its bulk mineral resources.